Additive Manufacturing: Polymers Applicable for Laser Sintering (LS). (2016) - Schmid, Manfred; Wegener, Konrad
Abstract: Additive Manufacturing (AM) is close to become a production technique changing the way of part fabrication in future. Enhanced complexity and personalized features are aimed. The expectations in AM for the future are enormous and betimes it is considered as kind of the next industrial revolution. Laser Sintering( LS) of polymer powders is one component of the AM production techniques. However materials successfully applicable to Laser Sintering( LS) are very limited today. The presentation picks up this topic and gives a short introduction on the material available today. Important factors of polymer powders, their significance for effective LS processing and analytical approaches to access those values are presented in the main part. Concurrently the exceptional position of polyamide 12 powders is this connection is outlined.